Sodium-glucose cotransporter-2 inhibitors and dipeptidyl peptidase-4 inhibitors on diabetic macular edema and the need for intravitreal injection - Yoo-Ri Chung; Chungwoon Kim; Eunzee Lee; Kihwang Lee (International Journal of Ophthalmology)
AIM: To investigate the effects of dipeptidyl peptidase-4 inhibitors (DPP4i) and sodium-glucose cotransporter-2 inhibitors (SGLT2i) on diabetic macular edema (DME) and the need for intravitreal injections (IVT) in patients with type 2 diabetes. METHODS: Data were retrospectively collected from the medical records of patients with diabetic retinopathy (DR) taking either DPP4i or SGLT2i as secondary oral hypoglycemic agents in addition to metformin between January 2019 and July 2022. We compared the prevalence of DME and the need for IVT among patients treated with DPP4i or SGLT2i. Propensity score matching was performed using the following variables: age, duration of diabetes, blood glucose control (HbA1c) level, and severity of DR. RESULTS: A total of 268 patients with DR were included in this study. More DPP4i users needed IVT than SGLT2i users (35.3% vs 18.0%, P=0.011), while the prevalence of DME was not different. The use of SGLT2i was associated with a lower need for IVT than DPP4i [odds ratio (OR) 0.404, 95% confidence interval (CI) 0.198–0.823], and similar trends were observed after propensity score matching (OR 0.419, 95%CI 0.181–0.970). However, this tendency was not significant in multiple logistic regressions. For DME, the use of DPP4i was not a significant risk factor compared to SGLT2i. CONCLUSION: The use of SGLT2i may be associated with a lower need for IVT for overall DR complications, while other factors may contribute to this effect. The effect of SGLT2i on the prevention of DME is not evident.